THE RELATIONSHIP BETWEEN MANAGEMENT OF HOUSEHOLD WASTE WITHDIARCIAN EVENTS IN CHILDREN AT SINDANG BARANG BOGOR: HUBUNGAN PENGELOLAAN SAMPAH RUMAH TANGGA DENGAN KEJADIAN DIARE PADA BALITA DI KELURAHAN SINDANG BARANG KOTA BOGOR - Bunga Oktora (Jurnal Ilmiah Wijaya, 2018)
Diarrhea causes 801,000 child deaths each year or kills 2,195 children per day. Environmental factors also determine the good and bad health of a person and the community, one of which is garbage disposal (waste management). Based on a preliminary study conducted by researchers in the Sindang Barang Village of 10 housewives who have children under five, all have experienced diarrhea. As for the management of household waste from 10 housewives surveyed there are 2 housewives with good household waste management and 8 housewives with poor household waste management. The purpose of this study was to analyze the relationship between household waste management and the incidence of diarrhea in toddlers in Sindang Barang Village, Bogor City in 2017. This type of research is a quantitative analytic study with a cross-sectional design and a cross-sectional approach. The method of sampling in this study uses the technique of cluster sampling with a sample of 301 respondents. Data collection was obtained through questionnaires. Based on the results of the study showed that of 301 respondents there is good household waste management as many as 128 respondents (42.5%) toddlers without diarrhea and 8 respondents (2.66%) diarrhea toddlers. The statistical test results with asignificance level of α 0.005 to obtain a p value of 0,000 <0.005 and a closeness value of -0.456. So that,it can be concluded that there is a relationship between household waste management and the incidence of diarrhea in infants in Sindang Barang KotaBogor in 2017. At least, good household waste management can prevent diarrheal diseases in infants,and this researchis expected for educational institutions and local governments as well as the community can improved orupdatedtheirinformation about waste management and diarrhea events, so as to strive to apply the waste management stage correctly and have an impact improving the quality of public health and decreasing cases of diarrhea in infants.